Reimagining the academic library - Lewis, David W., 1951- (Rowman and Littlefield, 2016)
"Academic libraries are in the midst of significant disruption. Academic librarians and university administrators know they need to change, but are not sure how. Bits and pieces of what needs to happen are clear, but the whole picture is hard to grasp. Reimagining the Academic Library paints a simple straightforward picture of the changes affecting academic libraries and what academic librarians need to do to respond to the changes would help to guide future library practice. The aim is to explain where academic libraries need to go and how to get there in a book that can be read in a weekend. David Lewis provides a readable survey of the current state of academic library practice and proposes where academic libraries need to go in the future to provide value to their campuses. His primary focus is on collections as this is the area with the greatest opportunity for change and is the driver of most library cost. Lewis provides an accessible framework for thinking about how library practice needs to adjust in the digital environment. The book will be useful not only to academic librarians, but also for librarians to share with presidents and provosts who a concise source for understanding where and how to focus their expenditures on libraries."--Provided by publisher.